Alkoxo and aryloxo derivatives of metals - Bradley, D. C. (Academic Press, 2001)
Alkoxo and Aryloxo Derivatives of Metals gives a comprehensive account of the chemistry of metal alkoxides and metal aryloxides, including their industrial applications such as microelectronics, ceramics, nonlinear optical materials, high-temperature superconductors, specialized glasses, and other advanced novel materials. It is an invaluable reference source book. The book is an updated edition of Metal Alkoxides, published by Academic Press in 1978, with additional coverage of metal aryloxides. It reflects the enormous growth in interest in this field in recent years. Alkoxo and aryloxo derivatives are organic compounds with metals for useful industrial purposes. Alkoxo and Aryloxo Derivatives of Metals will appeal to a wide-ranging audience, including university researchers and chemistry graduate students in industrial laboratories concerned with microelectronics, ceramics, glasses and other advanced novel materials; any laboratories doing research on nonlinear optical materials, high-temperature superconductors, ceramic materials, and specialized glasses. It can also serve as a supplementary text for final year courses in advanced inorganic chemistry, e.g., metallo-organic chemistry.